Strategi Operasional Dalam Mengelola Produksi Dan Pengiriman Tepat Waktu Dalam Bisnis Sablon - Saputro, Bayu; Huda, Miftakul; Qoniatusholikha; Andini, Septia Nur; Alfariji, Midi (Innovative: Journal Of Social Science Research, 2025)
Ensuring on-time production and delivery is a major challenge in the screen printing business which relies heavily on customer orders with tight deadlines. Many screen printing business actors often face obstacles such as immature production planning, limited production capacity, and unstable supply of raw materials. These problems are exacerbated by less effective communication, limited workforce skills, as well as technical constraints such as broken machines and printing errors. Delays in delivery not only affect inside operations, but also lower customer trust and damage business reputation. In addition, operational costs often swell due to overtime needs and expensive express delivery. Therefore, an effective operational strategy is needed to maintain smooth production and delivery in the screen printing business.